The H2A.Z-associated protein ZNF512B acts as a transcriptional repressor, aggregates chromatin and binds RBBP4 via an alternative NuRD interaction motif - Wunderlich, Tim Marius; Justus Liebig University Giessen (My University, 2024)
Chromatin serves as the substrate for a multitude of essential biological functions within the cell and is dynamically regulated, for instance through the incorporation of histone variants. The evolutionarily conserved histone variant H2A.Z is involved in nearly all DNA-related processes but the mechanisms underlying its diverse roles remain largely unknown. One potential approach for further elucidation of these mechanisms is the investigation of H2A.Z-specific interacting proteins. Recently, the zinc finger (ZF) protein ZNF512B has been identified as an interactor of H2A.Z and its associated proteins HMG20A and PWWP2A. This study demonstrates that elevated levels of ZNF512B induce protein and chromatin aggregation in the nucleus, presumably facilitated by DNA binding and oligomerization of its ZF domains. Biochemical and mass spectrometry-based experiments show that ZNF512B interacts with the nucleosome remodeling and deacetylase (NuRD) complex. The solved crystal structure of ZNF512B bound to the NuRD member RBBP4 and biophysical assays reveal an alternative, internal NuRD interaction motif as necessary for this high-affinity interaction. Moreover, transcriptome analyses and reporter assays identify ZNF512B as a transcriptional repressor acting in NuRD-dependent and -independent manners. Collectively, this study may have implications for diseases in which ZNF512B expression is deregulated, such as neurodegenerative diseases and cancer, suggests the existence of additional proteins as potential NuRD interactors and contributes to a better understanding of the mechanisms underlying H2A.Z’s activity.
Keywords: H2A.Z; Chromatin; ZNF512B; NuRD; RBBP4; ddc:570